Examining the Impact of International Financial Reporting Standards Adoption on Financial Reporting Quality of Multinational Companies - Amar Johri (International Journal of Financial Studies)
This research delves into the influence of adopting international financial reporting standards (IFRSs) on the financial reporting quality (FRQ) of Indian multinational corporations (MNCs). It also investigates the moderating impact of the internal control system (ICS) on the relationship between IFRSs and FRQ. The data collection involves a survey using a previously validated and adjusted scale from earlier studies. A sample of 512 participants is selected through purposive sampling methods. The analysis employs partial least square structural equation modelling (PLS-SEM) to validate the data and test the hypotheses. The results indicate a significantly positive influence of perceived benefits, perceived ease of implementation, and government policy on IFRS adoption within Indian MNCs. However, the impact of legal requirements on IFRS adoption in Indian MNCs is insignificantly positive. Furthermore, adopting IFRSs substantially positively affects FRQ within Indian MNCs. Similarly, FRQ significantly positively affects the relevance, accuracy, understandability, comparability, and timeliness of MNCs’ financial reports in India. The moderating role of the ICS in the connections between IFRS adoption and FRQ is positive yet insignificant within Indian MNCs. The insights derived from this study are valuable for investors, shareholders, government authorities, financiers, board members, and top executives of organisations.